SYSTEMATIC LITERATURE REVIEW: KAJIAN ETNOMATHEMATICS IN TRADITIONAL MUSICAL INSTRUMENTS - Rabiatul Adawiah; Aan Putra (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
The need to refer to culture to make it easier for students to plant mathematical concepts in understanding mathematics learning materials. One of them is a traditional musical instrument. This study aims to identify and analyze ethnomathematical studies on traditional musical instruments and their relation to mathematical concepts. The research method used in this study is the Systematic Literature Review (SLR) method. Data collection was carried out by reviewing all articles related to ethnomathematics on traditional musical instruments used published in the period 2016-2021 The articles used in this study were 24 articles in accredited national journals obtained from the Google Schoolar database. The results showed that there were many traditional musical instruments that can be applied in learning mathematics, generally in geometry. It is hoped that further research can include improved skills for students.Keywords: Ethnomathematics, Traditional Musical Instruments, Siystematic LiteratureReview